2020
DOI: 10.1029/2020jb019445
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Fracture Network Evolution in Organic‐Rich Shale With Rapid Internal Fluid Generation

Abstract: When low‐permeability and organic‐rich rocks such as shale experience sufficient heating, chemical reactions including shale dehydration and maturation of organic matter lead to internal fluid generation. This may cause substantial pore fluid overpressure and fracturing. In the vicinity of igneous intrusions emplaced in organic‐rich shales, temperatures of several hundred degrees accelerate these processes and lead to intense fracturing. The resulting fracture network provides hydraulic pathways, which allow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Yan et al [20] found that as the angle between the direction of wellbore axis and the maximum horizontal stress increases, the pressures of fracture initiation and propagation grow. Rabbel et al [21] found that the fracture opening and propagation mode are related to the magnitude of external stress anisotropy, and strongly anisotropic far-field stresses lead to highly directional connectivity, which may translate to anisotropic fracture permeability. Liu et al [22] developed a novel fracability evaluation model of hydratebearing sediments integrating hydrate saturation, brittleness, stress anisotropy, and mineral composition.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [20] found that as the angle between the direction of wellbore axis and the maximum horizontal stress increases, the pressures of fracture initiation and propagation grow. Rabbel et al [21] found that the fracture opening and propagation mode are related to the magnitude of external stress anisotropy, and strongly anisotropic far-field stresses lead to highly directional connectivity, which may translate to anisotropic fracture permeability. Liu et al [22] developed a novel fracability evaluation model of hydratebearing sediments integrating hydrate saturation, brittleness, stress anisotropy, and mineral composition.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge, few if any numerical studies have yet been performed to simulate the development of nonplanar 3‐D fracture swarms, except for several attempts in investigating the evolution of 2‐D planar/nonplanar fracture networks (Z. Fan et al., 2014; Jin et al., 2010; Rabbel et al., 2020; Vega et al., 2020). Previous numerical and experimental studies have recognized that development of the fracture networks will experience the following three stages: (1) individual growth; (2) interaction and coalescence; and (3) loss of fluid overpressure and fracture aperture (Kobchenko et al., 2011;2014; Rabbel et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Fan et al., 2014; Jin et al., 2010; Rabbel et al., 2020; Vega et al., 2020). Previous numerical and experimental studies have recognized that development of the fracture networks will experience the following three stages: (1) individual growth; (2) interaction and coalescence; and (3) loss of fluid overpressure and fracture aperture (Kobchenko et al., 2011;2014; Rabbel et al., 2020). Although 2‐D models are useful for quantifying the onset, propagation, coalescence, and evolution of fluid‐driven fracture networks (Vega et al., 2020) and the 2‐D results are easy to comprehend and visualize (Rabbel et al., 2020), absence of the third dimension would lead to a potential knowledge gap that may impede a better understanding of realistic patterns of interacting fracture swarms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations